FAKTOR-FAKTOR YANG MEMPENGARUHI JUMLAH UANG BEREDAR DI INDONESIA PERIODE 1990-2010 - PRAWIDYA HARIANI RS (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2014)
In this study, the authors raised the heading "Factors Affecting Money Supply In Indonesia Period 1991-2010". This was raised because of the money supply has increased each year, while growth fluctuates, therefore, the authors are interested in analyzing what factors wrote that influence the money supply in Indonesia. The main objective of this study was to determine the effect of gross domestic product (GDP), SBI rates and gross domestic fixed capital formation on the money supply. The study was conducted in Indonesia by using secondary data with time series 1991-2010, which is sourced from the central body of statistics (BPS) and Bank Indonesia (BI). Data analysis model is equation econometric model with Ordinary Least Square method (OLS) by using SPSS 16 as a data processor of research. Based on estimates, that peroduk gross domestic product (GDP) and gross domestic fixed capital formation and significant positive effect on the money supply in Indonesia. The SBI rates negative and statistically significant on the money supply in Indonesia.